Effects of teaching concept mapping using practice, feedback, and relational framing. (April 2018) - Roessger, Kevin M.; Daley, Barbara J.; Hafez, Duaa A.
Abstract: Although concept mapping remains widely used in education, there is little research showing how best to teach it. We investigated if practice, feedback, and knowledge of relational framing help improve students' concept mapping skills over time. Four online graduate courses at two universities were randomly assigned to one of two teaching conditions: a traditional concept map teaching strategy or traditional plus relational framing teaching strategy. Students in each course created three concept maps over three weeks following repeated instruction and instructor feedback. Repeated practice and feedback improved the structural quality of students' concept maps, as well as the number of autobiographical elaborations within those maps. Teaching strategy moderated the effect of practice and feedback on the relational quality of students' maps. Relational scores in relational framing groups improved over time, whereas those in the traditional groups remained unchanged. Implications for teaching concept mapping are discussed. Highlights: Practice and feedback improves the structural quality of concept maps. Practice and feedback increases autobiographical elaboration in concept maps. Relational framing instruction improves the relational quality of concept maps. Traditional instruction fails to improve concept maps' relational quality.